2019
DOI: 10.1016/j.rmcr.2019.100906
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis in a patient clinically diagnosed with silicosis; is silica associated sarcoidosis a new phenotype?

Abstract: A diagnosis of silicosis is made on the basis of exposure and typical radiological findings, according to the ILO's International Classification of Radiographs of Pneumoconiosis. Radiological patterns of silicosis can, however, resemble sarcoidosis. Sarcoidosis is a multi-systemic disorder of unknown etiology, although a role for initiating inorganic triggers such as metals or silica has been suggested. In this case report, we illustrate a patient previously diagnosed with silicosis based on exposure and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…Among the inorganic dust particles most consistently associated with increased risk for sarcoidosis are respirable crystalline silica (RCS) and silicates. 10,[15][16][17][18][19][20][21][22] Case Reports: Kawano-Dourado et al 15 27 In the 12-month period following exposure, the incidence rate was 86 per 100,000; and in 2015, the average annual incidence rate was 25 per 100,000. 27,28 During the period 1985 to 1998, Prezant et al 29 observed an average annual incidence rate among NYC firefighters of 12.9 per 100,000, with a range of 0 to 43.6 per 100,000.…”
Section: Silica and Silicatesmentioning
confidence: 99%
“…Among the inorganic dust particles most consistently associated with increased risk for sarcoidosis are respirable crystalline silica (RCS) and silicates. 10,[15][16][17][18][19][20][21][22] Case Reports: Kawano-Dourado et al 15 27 In the 12-month period following exposure, the incidence rate was 86 per 100,000; and in 2015, the average annual incidence rate was 25 per 100,000. 27,28 During the period 1985 to 1998, Prezant et al 29 observed an average annual incidence rate among NYC firefighters of 12.9 per 100,000, with a range of 0 to 43.6 per 100,000.…”
Section: Silica and Silicatesmentioning
confidence: 99%
“…In the case of suspected TB, PCR is a rapid solution for the sputum sample where with a positive result we can immediately start therapy. In the case of TB we can have endobronchial lesions which have granulomas and the pathology report alone cannot distinguish sarcoidosis versus TB versus silicosis [ 8 , 19 ]. Other laboratory findings such as ACE or the bronchoalveolar lavage can assist us in the diagnostic workup of sarcoidosis; however, they assist as surrogate markers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silica exposure has been associated with sarcoidosis or sarcoid-like granulomatous lung disease (8)(9)(10)(11)(12)(13). Epidemiological studies have noted a high incidence of sarcoidosis in patients with silica exposure (10,11).…”
Section: A B C D Ementioning
confidence: 99%
“…Inhalation of beryllium can cause granulomatous lung disease that mimics sarcoidosis (7), and other metals and inorganic dust have also been associated with a granulomatous response (4)(5)(6). Silica might be a trigger for sarcoidlike granulomatous lung disease, and several studies have reported the association between silica exposure and sarcoidosis or sarcoid-like granulomatous lung diseases (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%